The Relationship Between Social Support and Push Bike Exercise Motivation - Muhammad Ulil Absor; Fery Darmanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study was motivated by the observed differences in the levels of motivation among children aged 2–8 years participating in push bike training at the Pushbike Academy in Purworejo, which are believed to be influenced by social support from their immediate environment. The study aims to analyze the relationship between social support from parents, coaches, and peers and children’s motivation for push bike sports. The study employed a mixed-methods approach with a descriptive design. The study subjects were children aged 2–8 years participating in push bike training, as well as parents and coaches serving as supporting informants. Data collection techniques included observation, interviews, questionnaires, and documentation, while data analysis utilized descriptive statistics (SPSS) and qualitative analysis (NVivo). The results showed that social support, particularly direct involvement, emotional support, and instrumental support from parents, was significantly associated with increased motivation in children to participate in push bike training on a sustained basis. It was concluded that family social support plays a crucial role in enhancing children’s motivation for sports from an early age.